Railways, Social Mobility, and Colonial Urbanization: Bogor in the Early Twentieth Century - Thariq Syah, M Kautsar; Hidayat, Asep Achmad; Supendi, Usman; Sa'adah, Putri Lailatus; Nurcahya, Yan; Mostafa, Mohamed Abd El Motaleb (TEMALI : Jurnal Pembangunan Sosial, 2026)
This article examines changes in social mobility in Bogor following the introduction of railways in the early twentieth century by positioning rail transport as a key infrastructure in the process of colonial urbanization. The study demonstrates that railway construction in Bogor cannot be understood merely as a technical innovation in transportation, but rather as an economic–political instrument that integrated the hinterland into the administrative and economic networks of the Dutch East Indies. Using a historical approach grounded in colonial archival sources and secondary references in the form of peer-reviewed academic articles and credible media reports, this research analyzes the relationship between railway development, social mobility, and the transformation of urban space during the period 1900–1930. The findings show that railways operated as a colonial mobility regime that simultaneously expanded horizontal mobility among indigenous populations—through intensified spatial movement and occupational diversification—while failing to open vertical mobility in an equitable manner. Access to education, official positions, and social status remained constrained by colonial structures based on race and class. In addition, railway lines and stations functioned as urban nodes that reconfigured the spatial organization of Bogor according to the logic of timetables, economic extraction, and colonial administration. Consequently, mobility and urbanization in Bogor were produced in a differential manner through colonial infrastructure that both accelerated movement and normalized social inequality. This article argues that railways functioned as a politically charged agent of social change and contributes to the historiography of colonial transportation in Indonesia through an analytical lens centered on mobility, power, and social stratification.